The effect of cryogenic carbon dioxide cooling on surface integrity of titanium alloy in turning - Razak, Muhammad Shahmi (2021)
High-speed turning is one of the most important methods in advanced manufacturing technology due to its speed which is three times the conventional speed value. The material that generally used in high speed turning is titanium alloy. The superior attractive properties of titanium alloy (Ti-6Al-4V) such as good mechanical and chemical properties, excellent corrosion resistance and high strength-to-weight ratio make it favorable in wide range of applications such as automotive, aerospace, medical and chemical industries. However, machining of this titanium alloy are known to cause the damaged of the surface due to their poor machinability as well as high cutting temperature using conventional cutting fluids as coolant. In this study, cryogenic carbon dioxide CO2 cooling has been used during turning Ti-6Al-4V ELI (extra-low interstitial). The objective of this research is to analyse the effect of cutting parameters towards surface integrity such as surface roughness, surface hardness, and microstructure of the material. This research focuses on developing a mathematical model for surface roughness of machined surface. Then, the generated mathematical model was used to optimize the cutting parameters in producing the best surface roughness value. The Sandvik uncoated carbide insert, CNGG 120408-SGF-H13A was selected as a cutting tool in high speed turning of titanium alloy Ti-6Al- 4V ELI with the hardness of 32 HRC by using 3-axis Computer Numerical Control (CNC) lathe Haas ST-20 lathe machine. The Response Surface Methodology (RSM) design of experiment using Box- Behnken was used to accommodate the turning experiment factors and levels towards surface roughness. Turning parameters studied were cutting speed (120, 170, 220 m/min), feed rate (0.1, 0.15, 0.2 mm/rev) and depth of cut (0.4, 0.5, 0.6 mm). There are 17 runs of machining parameters generated by Design Expert software using RSM Box-Behnken. The surface roughness values were measured for each 20 mm on the workpiece until flank wear (Vb) reaches the tool life criterion followed by JIS B4011-1971 standard. Based on the conducted investigation, it was found that the lowest surface roughness value 0.49 μm was achieved at the run 6; 220 m/min of cutting speed, 0.1 mm/rev of feed rate and 0.5 mm of depth of cut. The Analysis of Variance (ANOVA) shows that feed rate was the dominant factor that affects machining performance. The optimum parameter was achieved at 220 mm/min of cutting speed, 0.1 mm/rev of feed rate and 0.4 mm of depth of cut. The residual errors for surface roughness value of optimum parameters fell within 1.8% and 3.8% which are less than 10%. The microstructures of the surface and sub-surface have been changed in terms of volume fraction of β phase, compared to the as-received material. The surface hardness occurs due to hardening work caused by the low temperature at the cutting zone that comes from cryogenic cooling.